Does organisational culture influence human behaviour at work? - Kumar M., Dileep; Pandya, Srota; Bhatti, Muhammad Awais (RS Publication, 2012)
This article attempts to bring to the surface some key aspects, which closely related to the culture of the organisation.The article relates many key result areas, where the organisational culture influences the human behaviour at work.Work motivation, leadership, team work, organisational efficiency, organisational development, organisational changes etc., all are related to the beliefs and assumptions members have towards the prevalent organisational culture.The success of an organisation greatly depends how organisational members integrate the belief system and widely shared assumptions about work and work values.This article is based on the theoretical underpinnings, and the experience the author felt during his doctoral thesis work on impact of organisational culture upon employee‟s behaviour.